Evaluation of efflux pump activity and biofilm formation in multidrug resistant clinical isolates of Pseudomonas aeruginosa isolated from a Federal Medical Center in Nigeria - Florence Chijindu Ugwuanyi; Abraham Ajayi; David Ajiboye Ojo; Adeyemi Isaac Adeleye; Stella Ifeanyi Smith (BMC, 2021)
Abstract Background Pseudomonas aeruginosa an opportunistic pathogen, is widely associated with nosocomial infections and exhibits resistance to multiple classes of antibiotics. The aim of this study was to determine the antibiotic resistance profile, biofilm formation and efflux pump activity of Pseudomonas strains isolated from clinical samples in Abeokuta Ogun state Nigeria. Methods Fifty suspected Pseudomonas isolates were characterized by standard biochemical tests and PCR using Pseudomonas species -specific primers. Antibiotic susceptibility testing was done by the disc diffusion method. Efflux pump activity screening was done by the ethidium bromide method and biofilm formation assay by the tissue plate method. Genes encoding biofilm formation (pslA & plsD) and efflux pump activity (mexA, mexB and oprM) were assayed by PCR. Results Thirty-nine Pseudomonas spp. were identified of which 35 were Pseudomonas aeruginosa and 4 Pseudomonas spp. All 39 (100%) Pseudomonas isolates were resistant to ceftazidime, cefuroxime and amoxicillin-clavulanate. Thirty-six (92%), 10(25.6%), 20 (51.2%), 11(28%) and 9(23%) of the isolates were resistant to nitrofurantoin, imipenem, gentamicin, cefepime and aztreonam respectively. All the isolates had the ability to form biofilm and 11 (28%) of them were strong biofilm formers. They all (100%) harboured the pslA and pslD biofilm encoding genes. Varied relationships between biofilm formation and resistance to ciprofloxacin, ofloxacin, cefixime, gentamicin, imipenem, and aztreonam were observed. Only 23(59%) of the Pseudomonas isolates phenotypically exhibited efflux pump activity but mexA gene was detected in all 39 (100%) isolates while mexB and oprM genes were detected in 91%, 92%, and 88% of strong, moderate and weak biofilm formers respectively. Conclusion Multidrug resistance, biofilm and efflux pump capabilities in Pseudomonas aeruginosa have serious public health implications in the management of infections caused by this organism.